ANALYSIS OF LEARNING THROUGH WEB-BASED TUTORIALS (TUWEB) DURING THE COVID 19 PANDEMIC ON STUDENTS OF UPBJJ UT MEDAN - Hernawi Silalahi; Kula Ginting; Johannes Johannes (Sensei International Journal of Education and Linguistic, 2022)
The tutorial process or online lectures are a solution in learning in the post-pandemic era, especially at the Terbuka University in the Class Action Research writing course to reduce the spread of the corona virus. The web tutorial process is carried out online by utilizing the Microsoft Teams application and e-learning, which combines synchronous and asynchronous online for two hours in one meeting. This study aims to determine the analysis and response of students to online tutorials during the Covid-19 pandemic which requires students to do distance learning. The subject of this research is the 3rd semester of BI class, totaling 23 students. The findings during the tutorial show that there is active learning between tutors and students during online learning/TUWEB through Whatsapp Groups, LMS and Microsoft Teams.